Quality assurance as a foundational element for an integrated system of dementia care: Perspectives from physicians and geriatricians. Issue 6 (8th July 2019) - Heckman, George A.; Crutchlow, Lauren; Boscart, Veronique; Hillier, Loretta; Franco, Bryan; Lee, Linda; Molnar, Frank; Seitz, Dallas; Stolee, Paul
Abstract : Purpose: Many countries are developing primary care collaborative memory clinics (PCCMCs) to address the rising challenge of dementia. Previous research suggests that quality assurance should be a foundational element of an integrated system of dementia care. The purpose of this paper is to understand physicians' and specialists' perspectives on such a system and identify barriers to its implementation. Design/methodology/approach: The authors used interviews and a constructivist framework to understand the perspectives on a quality assurance framework for dementia care and barriers to its implementation from ten primary care and ten specialist physicians affiliated with PCCMCs. Findings: Interviewees found that the framework reflects quality dementia care, though most could not relate quality assurance to clinical practice. Quality assurance was viewed as an imposition on practitioners rather than as a measure of system integration. Disparities in resources among providers were seen as barriers to quality care. Greater integration with specialists was seen as a potential quality improvement mechanism. Standardized electronic medical records were seen as important to support both quality assurance and clinical care. Practical implications: This work identified several challenges to the implementation of a quality assurance framework to support an integrated system of dementia care. Clinicians require education to better understand quality assurance. Additional challenges include inadequate resources, a need for closer collaboration between specialists and PCCMCs, and a need for a standardized electronic medical record. Originality/value: Greater health system integration is necessary to provide quality dementia care, and quality assurance could be considered a foundational element driving system integration.